2006
DOI: 10.1088/0953-8984/18/43/010
|View full text |Cite
|
Sign up to set email alerts
|

The origin of ferromagnetism in57Fe ion-implanted semiconducting 6H-polytype silicon carbide

Abstract: Semiconducting (mostly p-doped) single crystals of the 6H-polytype of α-SiC(0001) were implanted with 57Fe ions with a nominal dose of 1.0 × 1016, 2.0 × 1016, 3.0 × 1016 or 2.0 × 1017 cm−2 (high-dose sample p-hd) at 100 or 200 keV ion energy in order to produce diluted magnetic semiconductors (DMSs). After implantation all samples (except p-hd) were subject to rapid thermal annealing at 1000 °C for 2 min. The structure was investigated by x-ray diffraction, high-resolution cross-sectional transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 54 publications
5
28
0
1
Order By: Relevance
“…Various impurity complexes can coexist in a statistical distribution, further complicating the physical picture. Contribution of secondary phases to the magnetic signal can also not be ruled out completely (Stromberg et al, 2006). SiC doped with Mn received more attention from the experimentalists compared to the other SiC DMSs and the reported promise of this impurity for obtaining high Curie temperatures is in-line with our conclusions.…”
Section: Concluding Remarks and Outlooksupporting
confidence: 87%
See 2 more Smart Citations
“…Various impurity complexes can coexist in a statistical distribution, further complicating the physical picture. Contribution of secondary phases to the magnetic signal can also not be ruled out completely (Stromberg et al, 2006). SiC doped with Mn received more attention from the experimentalists compared to the other SiC DMSs and the reported promise of this impurity for obtaining high Curie temperatures is in-line with our conclusions.…”
Section: Concluding Remarks and Outlooksupporting
confidence: 87%
“…Nevertheless, the existence of free holes may have led to an additional, hole-mediated exchange interaction playing the role in stabilizing ferromagnetism at larger distances between the impurities. At least some of the experimental studies of Fe-doped SiC reported ferromagnetic DMS behaviour in Fe-implanted 6H-SiC (Theodoropoulou et al, 2002;Stromberg et al, 2006). Our calculations reveal nonmagnetic ground state and antiferromagnetic ordering in the magnetic state of (Si, Fe) C. Such discrepancy may be explained by several factors.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 57%
See 1 more Smart Citation
“…Theodoropoulou et al showed that 5% of Fe atoms implanted in the 6H-SiC polytype lead to a ferromagnetic material at a temperature of about 250 K. 11 No secondary phase was detected in their samples. Similar findings have been reported by Pearton et al 12 and Stromberg et al 13 Indeed, these authors carried [14][15][16] The formation of nano-sized particles of nano-metric size is partly responsible for the magnetic properties observed on their samples after annealing.…”
Section: Introductionsupporting
confidence: 85%
“…The origin of the magnetism in their samples was not clear, and the authors point out that further experiments are needed to identify the origin of the magnetism [179]. Later work on Fe-doped 6H-SiC by Stromberg et al [180] using Fe ion implantation, and Song et al [181] using polycrystalline powders, identified the formation of Fe 3 Si precipitates in their samples and suggested that the ferromagnetic magnetization appearing near room temperature was due to this phase.…”
Section: Sic-based Magnetic Semiconductorsmentioning
confidence: 99%